If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -11 + 51 = -4(x + 5) Combine like terms: -11 + 51 = 40 40 = -4(x + 5) Reorder the terms: 40 = -4(5 + x) 40 = (5 * -4 + x * -4) 40 = (-20 + -4x) Solving 40 = -20 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 40 + 4x = -20 + -4x + 4x Combine like terms: -4x + 4x = 0 40 + 4x = -20 + 0 40 + 4x = -20 Add '-40' to each side of the equation. 40 + -40 + 4x = -20 + -40 Combine like terms: 40 + -40 = 0 0 + 4x = -20 + -40 4x = -20 + -40 Combine like terms: -20 + -40 = -60 4x = -60 Divide each side by '4'. x = -15 Simplifying x = -15
| -30x+12(x-1)=24x+2 | | 875/x/60=26.25 | | 7x=1/2*105 | | 5x-4=11+2n | | 9(3x-5)+9x= | | 3(x-4)=23-4c | | 3lnc=2lny | | 6+6x-2x=-10 | | 25t^2+45t=0 | | 5log(5x-10)=15 | | 3ln(2X)=27 | | 10(3x+12)+13x-14= | | 3h=-18 | | 48-5x=18 | | 3+4x+5x=48 | | 8(x-9)=15 | | -3+-b=1 | | 2x-(24/x)-8=0 | | x+2y-3=xy | | 15x^2-27y^2=12 | | 4(3x+7)=10 | | 7y+4(y-5)=4(y+1)-2 | | -7r=14 | | 3(5x+9)=37+19 | | x^2-27y^2=12 | | A^2+12a=-32 | | -3=p/6-6 | | 8a+-3=5 | | 3(2x+3)=2x-7 | | 7(4x-6)-7=28x-49 | | ln(x+2)+ln(x+4)=2 | | 3x+5x-4=4 |